Climate change influences on the potential geographic distribution of the invasive Asian longhorned tick, Haemaphysalis longicornis - Mohammed Okely; Ze Chen; Eslam Adly; Mahmoud Kamal (Scientific Reports)
Abstract The Asian long-horned tick, Haemaphysalis longicornis Neumann, 1901, is the competent vector for severe fever with thrombocytopenia syndrome virus (SFTSV). Haemaphysalis longicornis originated mainly in eastern Asia and invaded many areas like Australia, New Zealand, and the Pacific islands, and was recently introduced to eastern parts of the USA. This species is characterized by high adaptability to a wide range of temperatures and can reproduce parthenogenically under stressful conditions. Migratory birds are important hosts of H. longicornis and are thought to be responsible for its unexpected invasion and introduction into new areas worldwide. This study predicted the historical (near current) global environmental suitability and the possible shifts in environmental suitability for H. longicornis under the ongoing climate change between 2021 and 2100. The results demonstrated that Europe is at potential of high environmental suitability for H. longicornis invasion although this species has not been recorded in any regions of Europe yet. Our model also anticipated the environmental suitability for H. longicornis in eastern parts of the USA, although the recently recorded occurrences there were not used in the model calibration. Climate change is thought to affect and increase the range of suitable environments for H. longicornis. The different maps introduced in this study may help improve understanding of the global environmental suitability for this invasive disease vector and predict the areas at high environmental suitability for possible invasion to prioritize the control programs and enhance quarantine procedures in these areas.